Having a Job Is Not Enough to Escape Poverty: Case of Indonesian Working Poors - Ramadhani, Financy; Putra, Fajar Santoso (Institut Teknologi Sepuluh Nopember, 2019)
Having a job is apparently not enough to ensure that the person is able to make ends meet, because the problem of unemployment is actually not the main problem of eradicating poverty. Poor people do not have the privilege of not working, they inevitably have to work to earn income. But the income from the work they do is of low value, so it is unable to meet their needs, especially basic needs. About 8.25 percent of working population in Indonesia are working poor, meaning they work, but the income is not enough to meet the needs. Using 2018 National Socio Economic Survey (SUSENAS) data, this study tries to dissect the labor conditions in Indonesia. The working population is still dominated by workers with low education, and there are still many who work as family/unpaid workers showing as a form of inefficiency. The characteristics of poor workers in Indonesia are male, living in rural areas. Still in prime age range, but poorly educated, only at elementary school level or less. These characteristics at the individual level are closely related to the mechanism of low wages which makes a person more at risk of becoming a working poor.